Symbolic analysis detects alterations of cardiac autonomic modulation in congestive heart failure rats - Tobaldini, Eleonora (2009)
Congestive heart failure (CHF) is associated with neurohumoral activation. Only very few studies have examined the progression of autonomic dysfunction in CHF in humans and scanty data are available in animal models of CHF. This study was performed to assess the changes in cardiac autonomic modulation during the progression of CHF in a rat model, using an innovative analysis of heart rate variability. Progression of cardiovascular autonomic dysfunction was assessed in a rat model of CHF induced by coronary artery ligation. Spectral and symbolic analyses were performed on heart period (approximated with pulse interval, PI) and systolic arterial pressure (SAP) signals, acquired ~2 and ~4 weeks after the surgical procedure. As CHF developed, symbolic analysis revealed a decrease of rhythmical physiological sympathetic modulation, as indicated by the reduction of the percentage of stable patterns. In addition, symbolic analysis revealed that runs of short-long-short and/or long-short-long PI values and high-low-high and/or low-high-low SAP values were more and more frequent as CHF progressed. On the contrary, spectral analysis of PI and SAP series was not able to detect any impairment of autonomic regulation. Indeed, low frequency and high frequency powers derived from both PI and SAP series were not significantly changed. These data indicate that the autonomic cardiovascular modulation is altered during the progression of CHF and that symbolic analysis seems to be more suitable than spectral analysis to describe alterations of heart period dynamics and of cardiovascular regulation in this animal model of CHF.